Effortless awareness: using real time neurofeedback to investigate correlates of posterior cingulate cortex activity in meditators' self-report - Garrison, Kathleen; Santoyo, Juan; Davis, Jake; Thornhill, Thomas; Kerr, Catherine; Brewer, Judson (Frontiers in Human Neuroscience, 2013)
Neurophenomenological studies seek to utilize first-person self-report to elucidate cognitive processes related to physiological data. Grounded theory offers an approach to the qualitative analysis of self-report, whereby theoretical constructs are derived from empirical data. Here we used grounded theory methodology to assess how the first-person experience of meditation relates to neural activity in a core region of the default mode network –the posterior cingulate cortex. We analyzed first-person data consisting of meditators’ accounts of their subjective experience during runs of a real-time fMRI neurofeedback study of meditation, and third-person data consisting of corresponding feedback graphs of posterior cingulate cortex activity during the same runs. We found that for meditators, the subjective experiences of ‘undistracted awareness’ such as ‘concentration’ and ‘observing sensory experience’, and ‘effortless doing’ such as ‘observing sensory experience’, ‘not efforting’, and ‘contentment’, correspond with posterior cingulate cortex deactivation. Further, the subjective experiences of ‘distracted awareness’ such as ‘distraction’ and ‘interpreting’, and ‘controlling’ such as ‘efforting’ and ‘discontentment’, correspond with posterior cingulate cortex activation. Moreover, we derived several novel hypotheses about how specific qualities of cognitive processes during meditation relate to posterior cingulate cortex activity, such as the difference between meditation and ‘trying to meditate’. These findings offer novel insights into the relationship between meditation and self-related thinking and neural activity in the default mode network, driven by the first-person experience.